Strengthening the Islamic Boarding School-Based Economy and Entrepreneurship Towards Economic Independence (Case Study at the Al-Bahjah Sumber Islamic Boarding School, Cirebon Regency) - Fata, M. Anisul; Mnongya, Rosemary (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
Many Islamic boarding schools do not yet have economic independence, so the concept of Islamic boarding school independence must continue to be promoted not only for the internal interests of the Islamic boarding school, but also for the social interests of society, so that the existence of Islamic boarding schools can be felt by the community. This research aims to examine the strengthening of Islamic boarding school-based entrepreneurship towards economic independence in Pondok Al-Bahjah, Cirebon Regency. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, participant observation and documentation. The research results show three main findings, including: First, efforts to strengthen Islamic boarding school-based entrepreneurship are carried out through Economics and Entrepreneurship, creating products that are able to compete in the market, as well as improving skills in entrepreneurship. Second, factors that influence the success of entrepreneurship programs include good leadership and management, adequate human resources, entrepreneurship education, technology and innovation, supporting infrastructure and facilities, partnerships, monitoring and evaluation which are carried out regularly. Third, the impact of strengthening Islamic boarding school-based entrepreneurship is increasing the economic independence of students, developing students' skills, and improving the welfare of students and residents in the area around Islamic boarding schools. The implications of this study show that strengthening entrepreneurship in Al-Bahjah Islamic Boarding School, Cirebon Regency has an impact on three important areas: increasing the economic independence of the pesantren and the surrounding community through various business units, improving the welfare of students and the community by creating jobs, and developing entrepreneurial skills of students as a provision for their future. This changes the role of pesantren from just an Islamic educational institution to a social institution with strategic economic contribution.